EXECUTIVE POWER IN THEORY OF SEPARATION OF POWERS - Бородін, Іван Лук’янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: an attempt to analyze the executive power in the theory of separation of powers has been made. A historical aspect of the theoretical-legal phenomenon that is defined as the executive power has been considered. Methods: phenomenological, hermeneutic, comparative-legal, sociological, logical, dialectical. Results: the nature of such categories as «executive power», «legislative power», «state power», «public administration» has been shown. Their interrelation as separate types of legal thinking has been analyzed. Their necessity, importance, expediency, and actuality in the national state formation have been grounded. Discussion: the formation of executive power, as a theoretical-legal phenomenon, is one of the key factors of national state formation. The content of these processes reflects the perception of the constitutional principle of the separation of powers. The implementation of this principle promotes the democratic essence of state formation because a modern state exists under conditions promoted by the separation of powers. However, the organization of state rule on the principle of separation of powers can not be considered as sufficient for the assessment of the socio-political development. Particularities of the adopted form of state rule and the characteristics of the society in which a properly constructed state mechanism operates have a significant value. The formation of executive power in Ukraine is the subject of the analysis of representatives of various sciences. However, objectively, theoretical-legal is the most important one. The beginning of the present stage of constitutional regulation of the executive power is objectively connected with the official adoption and gradual introduction of the idea of powers separation at the level of state practice. This idea was reflected in the first domestic act of constitutional importance that is the Declaration of State Sovereignty of Ukraine. One of the provisions of this act stated that «state power in the Republic shall be exercised on the principle of its division into legislative, executive and judicial branches». This provision became programmatic for many party-political forces. All this reflected the political struggle to choose the direction of social development, in particular, the forms of statehood of Ukraine. For many politicians and scholars, accepting the idea of separation of powers and recognizing the need to put it into practice, in essence, means an awareness of Ukraine’s state self-sufficiency.